The effect of non-standard interactions and environmental decoherence at DUNE - Chinmay Bera; K. N. Deepthi; Rukmani Mohanta (Journal of High Energy Physics)
Abstract The Deep Underground Neutrino Experiment (DUNE) is a proposed long-baseline neutrino oscillation experiment that will project an on-axis wide-band neutrino beam over a distance of 1300 km to determine the unknowns in the neutrino sector. Given the baseline of 1300 km and the intense beam facility, DUNE is a promising experiment to study the sub-leading effects such as environmental decoherence, matter induced non-standard interactions (NSIs), neutrino decay, etc. In this study, we investigate how NSI and environmental decoherence affect the neutrino oscillation probabilities simultaneously. Considering the modified probabilities we obtain the updated mass hierarchy (MH) and CP violation (CPV) sensitivities of DUNE. Furthermore, we demonstrate the sensitivity of DUNE to distinguish between the effects of NSI and environmental decoherence.